Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 816511 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Carex L.", "BasisOfRecord is Specimen" ] } The dataset includes 816511 records from 270 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000312-150211104439307/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences